Staging History: The Arts at the “Independence Centenary International Exposition” (Rio de Janeiro, 1922-1923) - Carvalho, Danielle Crepaldi (Revista de História, 2022)
This article analyzes the artistic production realized during the “Independence Centenary International Exposition” (Rio de Janeiro, 1922-1923), the previous artistic production presented there, and finally, the production that took place outside the Exposition but established an indelible relationship with it. To this purpose, we analyzed numerous works from literature, theater, photography, film, music, and painting produced by various actors, also considering the architectural contributions, responsible for empirically erecting the buildings that housed the Exposition. Furthermore, we seek to understand how these buildings dialogue with the organization of event’s efforts to impose signs of nationality and a theater of modernity through them.